Epidemiology and Risk Factors of Portal Venous System Thrombosis in Patients With Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Lin, Hanyang; Bai, Zhaohui; Meng, Fanjun; Wu, Yanyan; Luo, Li; Shukla, Akash; Yoshida, Eric M.; Guo, Xiaozhong; Qi, Xingshun (Frontiers in Medicine, 2022)
Background: Inflammatory bowel disease (IBD) patients may be at a risk of developing portal venous system thrombosis (PVST) with worse outcomes. The present study aims to explore the prevalence, incidence, and risk factors of PVST among IBD patients. Methods: PubMed, EMBASE, and Cochrane Library databases were searched. All eligible studies were divided according to the history of colorectal surgery. Only the prevalence of PVST in IBD patients would be pooled, if the history of colorectal surgery was unclear. The incidence of PVST in IBD patients after colorectal surgery would be pooled, if the history of colorectal surgery was clear. Prevalence, incidence, and risk factors of PVST were pooled by only a random-effect model. Subgroup analyses were performed in patients undergoing imaging examinations. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. Results: Thirty-six studies with 143,659 IBD patients were included. Among the studies where the history of colorectal surgery was unclear, the prevalence of PVST was 0.99%, 1.45%, and 0.40% in ulcerative colitis (UC), Crohn’s disease (CD), and unclassified IBD, respectively. Among the studies where all patients underwent colorectal surgery, the incidence of PVST was 6.95%, 2.55%, and 3.95% in UC, CD, and unclassified IBD after colorectal surgery, respectively. Both prevalence and incidence of PVST became higher in IBD patients undergoing imaging examinations. Preoperative corticosteroids therapy (OR=3.112, 95%CI: 1.017-9.525; P=0.047) and urgent surgery (OR=1.799, 95%CI: 1.079-2.998; P=0.024) are significant risk factors of PVST in IBD patients after colorectal surgery. The mortality of IBD patients with PVST after colorectal surgery was 4.31% (34/789). Conclusion: PVST is not rare, but potentially lethal in IBD patients after colorectal surgery. More severe IBD, indicated by preoperative corticosteroids and urgent surgery, is associated with higher risk of PVST after colorectal surgery. Therefore, screening for PVST by imaging examinations and antithrombotic prophylaxis in high-risk patients should be actively considered.